Gaps in the Diagnosis and Treatment of Drug-resistant Tuberculosis in Mexico - Laniado-Laborín, Rafael; Castro-Mazon, Gerardo; Salcido-Gastélum, Jorge; Saavedra-Herrera, Nallely; Magaña-Ocaña, Julio; Luna-López, Fátima L. (Current Respiratory Medicine Reviews, 2024)
Objective: The study aimed to determine the critical gaps in the care of drug-resistant tuberculosis to implement strategies for its elimination. Material and Methods: Cases with various resistance profiles that were presented to the National Advisory Group for Drug Resistance during the years 2019-2022 have been described. Results and Discussion: 104 cases were included in this study. 41% of the patients had diabetes (41%) as a comorbidity. There have been observed delays in the reporting of rapid molecular tests; with the Xpert MTB/RIF, delays of 6.33 days have been reported. There have also been observed delays in the request for phenotypic drug susceptibility tests; from the time of initial diagnosis, patients have been found to receive their first drug susceptibility test, on average, after 20 months. The bacteriological follow-up during the treatment with monthly culture has been found to only be carried out in 8% of the cases. In the contact investigation, only 16% of the listed contacts had been studied for infection or active disease. Conclusion: The elimination of these gaps requires the decentralization of susceptibility tests for fluoroquinolones, shortening the times between the diagnosis of drug resistance and the start of treatment, a close clinical and bacteriological follow-up, and an exhaustive investigation of contacts.
Keywords: delays